Good Corporate Governance and Financial Performance in Its Influence on Profit Growth in Pharmaceutical Companies Listed on the Indonesia Stock Exchange - Bernike Yoan Filadelfia (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of Good Corporate Governance (GCG) as a proxy for managerial ownership, institutional ownership and independent board of commissioners on earnings growth. This study also examines the effect of financial performance as proxied by the current ratio, total asset turnover and return on assets on profit growth. The sample used is 9 pharmaceutical companies listed on the Indonesia Stock Exchange in 2016-2020. This study uses panel data regression analysis techniques to analyze the data. The results showed that managerial ownership, institutional ownership, independent board of commissioners and return on assets had a positive effect on profit growth. The current ratio variable has a negative effect on profit growth, while total asset turnover has no effect on profit growth.